Breeding systems and genetic diversity in tropical carpenter ant colonies: different strategies for similar outcomes in Brazilian Cerrado savanna - Azevedo-Silva, Marianne; Mori, Gustavo M. [UNESP]; Carvalho, Carolina S.; Cortes, Marina C. [UNESP]; Souza, Anete P.; Oliveira, Paulo S. (Oxford Univ Press, 2020)
Eusocial insects tend to present low genetic diversity (GD) within colonies, which can increase with the co-occurrence of multiple queens (polygyny) or with multiple mating by a single queen (polyandry). Therefore, it is important to elucidate how these strategies influence GD, which in turn mediate population ecology and how organisms respond to their environment. We studied two carpenter ant species from the Brazilian savanna, Camponotus renggeri and C. rufipes. Using microsatellites, we evaluated the number of breeders, the genetic relatedness and the contribution of polygyny and polyandry to GD within colonies. Both species exhibited facultative polygyny. In C. renggeri, low related queens formed colonies jointly and present low mating frequency. In this species, colony GD increased with the number of queens. Contrastingly, closely related queens of C. rufipes formed polygynous colonies, exhibiting high mating frequency. In C. rufipes, both queens and males contributed to colony GD. Despite the differences, the two species have similar GD at the colony scale. Under low mating frequency, our data support that polygyny has evolutionary importance for increasing GD in ant colonies, a mechanism mainly conferred to polyandry. Although the impact of GD in variable ecological and adaptive contexts remains uncertain, this study highlights how distinct reproductive strategies may generate similar patterns of GD in ants.
Keywords: breeding system strategy; Camponotus; colony genetic structure; polyandry, polygyny